KABUKI SYNDROME WITH EPILEPSY: CLINICAL CASE - N. Yu. Borovikova; K. S. Borovikov; K. Yu. Mukhin; M. B. Mironov (Эпилепсия и пароксизмальные состояния, 2016)
Kabuki syndrome is rare genetic disorder. Patients with this syndrome are phenotypically similar to Kabuki actors. The authors present a review article which describes the history, etiology, clinical features, diagnosis, and approaches to therapy of this syndrome. Special attention is description of a clinical case of Kabuki syndrome. Particularities of epilepsy clinical course, EEG patterns and treatment of girl with this syndrome were examined